IMPLEMENTATION OF THE LIVING QUR’AN: STRATEGIS FOR HABITUALIZING QUR’ANIC VALUES IN MADRASAH ALIYAH - Muhammad Abid Robiun Nuha; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the implementation of the Living Qur'an concept as a strategy for habituating Qur'anic values in Madrasah Aliyah. Living Qur'an is understood as a social practice that makes the Qur'an not only a normative text but also a guideline for life that is internalized in culture, customs, and the education system. This study uses a qualitative approach with a literature review. Data collection techniques were carried out through literature analysis, such as books, scientific articles, and research reports. Meanwhile, data analysis used content analysis. The results of the study show that the implementation of Living Qur'an is carried out through habituation strategies integrated into intracurricular, cocurricular, and extracurricular activities, such as the habit of reciting the Qur'an before learning, tahfidz programs, congregational prayers, Islamic holidays, and character building based on Qur'anic values. This strategy is supported by teacher role modeling, madrasah policies, and the creation of a conducive religious environment. The impact is evident in the improvement of students' religious character, discipline, responsibility, and the formation of an academic culture based on Qur'anic values. The implementation of Living Qur'an through habituation strategies is effective in shaping students' character holistically, covering spiritual, moral, and social aspects.